The CD8(+) memory T-cell state of readiness is actively maintained and reversible - Allam, Atef (American Society of Hematology, 2009)
The ability of the adaptive immune system to respond rapidly and robustly upon repeated antigen exposure is known as immunologic memory, and it is thought that acquisition of memory T-cell function is an irreversible differentiation event. In this study, we report that many phenotypic and functional characteristics of antigen-specific CD8 memory T cells are lost when they are deprived of contact with dendritic cells. Under these circumstances, memory T cells reverted from G(1) to the G(0) cell-cycle state and responded to stimulation like naive T cells, as assessed by proliferation, dependence upon costimulation, and interferon-γ production, without losing cell surface markers associated with memory. The memory state was maintained by signaling via members of the tumor necrosis factor receptor superfamily, CD27 and 4-1BB. Foxo1, a transcription factor involved in T-cell quiescence, was reduced in memory cells, and stimulation of naive CD8 cells via CD27 caused Foxo1 to be phosphorylated and emigrate from the nucleus in a phosphatidylinositol-3 kinase–dependent manner. Consistent with these results, maintenance of G(1) in vivo was compromised in antigen-specific memory T cells in vesicular stomatitis virus-infected CD27-deficient mice. Therefore, sustaining the functional phenotype of T memory cells requires active signaling and maintenance.